Effect of Mixing Temperature on The Utilization of Styrofoam Waste as An Additive in Asphalt Concrete"“Wearing Course (AC-WC) - Fitriansyah, Fahrul; Azwansyah, Heri; Mayuni, Siti (Jurnal Teknik Sipil, 2024)
Styrofoam is a polystyrene (PS) variant that contains chemicals harmful to humans. As a step to recycle, Styrofoam can be used as an added ingredient in asphalt mixtures. The research aimed to find the optimum asphalt content (KAO) value and analyze the effect of styrofoam addition and mixing temperature on the marshall parameters of AC-WC asphalt. The research used variations in mixing temperature of 130 °C, 150 °C, and 170 °C and variations in styrofoam content of 0%, 2%, 4%, 6%. The results of marshall testing of marshall parameters obtained the optimum asphalt content (KAO) value of 6.4%. Variations in mixing temperature with styrofoam content show that the mixture has changed marshall characteristics. The optimum stability value is obtained at a mixing temperature of 170 °C with a 4% styrofoam content of 979.61 Kg. The maximum flow value is found at 6% styrofoam content with a mixing temperature of 170 ° C by 3.13 mm. The maximum Marshall Quotient value is found at 4% styrofoam content with a mixing temperature of 170 °, amounting to 331.31 Kg/mm. The Void in the Mixture (VIM) value decreased to 4.16% as the styrofoam content increased, the Void in Mineral Aggregate (VMA) value decreased by 17.32% and the Void Filled with Asphalt (VFB) value increased by 80.35% as the styrofoam content increased, this can be explained because the use of significant levels of styrofoam reduces the volume of voids in the mixture and between aggregates. The high mixing temperature causes the asphalt and styrofoam to be more fluid, making it easier to envelop the aggregate and enter the mixture cavity.Keywords: Mixing temperature, Asphalt Concrete-Wearing Course, Styrofoam, Marshall Parameters, Additive material